Long‐term outcomes in African American kidney transplant recipients under contemporary immunosuppression: a four‐yr analysis of the Mycophenolic acid Observational REnal transplant (MORE) study. (24th December 2013) - Narayanan, Mohanram; Pankewycz, Oleh; Shihab, Fuad; Wiland, Anne; McCague, Kevin; Chan, Laurence
Abstract Mycophenolic acid Observational REnal transplant (MORE) was a prospective, observational study of de novo kidney transplant patients receiving mycophenolic acid (MPA). Four‐yr data on 904 patients receiving tacrolimus and enteric‐coated mycophenolate sodium (EC‐MPS) or mycophenolate mofetil (MMF) were analyzed to evaluate immunosuppression and graft outcomes in African American (AA, n = 218) vs. non‐AA (n = 686) patients. Mean tacrolimus dose was higher in AA vs. non‐AA patients but mean tacrolimus trough concentration was similar. Use of the recommended MPA dose in AA patients decreased from 78.9% at baseline to 33.1% at year 3. More AA patients received the recommended MPA dose with EC‐MPS than MMF at month 6 (56.2% vs. 35.7%, p = 0.016) and month 36 (46.6% vs. 16.7%, p = 0.029), with no safety penalty. Significantly, more AA patients received corticosteroids than non‐AA patients. Biopsy‐proven acute rejection was higher in AA vs. non‐AA patients (18.9% vs. 10.7%, p = 0.003), as was graft loss (10.9% vs. 4.4%, p = 0.003); differences were confirmed by Cox regression analysis. Patient survival was similar. Estimated GFR was comparable in AA vs. non‐AA patients. Kidney allograft survival remains lower for AA vs. non‐AA recipients even under the current standard of care.